Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) dalam Pembelajaran Matematika untuk Kelas Rendah - Chasnawati, Muthik (Institut Agama Islam Negeri (IAIN) Tulungagung, 2013)
Teachers must be creative in playing their role as educators including in the field of mathematics. Through the implementation and modification of teaching models, students are hoped to be a good and independent generation whoÂ are creative and innovative. One of the teaching models which may be used is Cooperative learning with Team Assisted Individualization (TAI)Â models.